Model Komunikasi Da’i dalam Meningkatkan Pengamalan Agama Muallaf Daerah Minoritas Desa Muzoi Kecamatan Lahewa Timur Kabupaten Nias Utara - Zebua, Ajniver Hamnur (Asian Journal of Islamic Studies and Da'wah, 2023)
This research aims to determine the communication model in increasing the practice of the religion of converts in the minority area of North Nias Regency and to find out the obstacles in the process of increasing the practice of the religion of converts in the minority area of North Nias Regency. This type of research is field research. In this research, I used a qualitative method, namely descriptive, by looking for actual and detailed data and information in a non-statistical manner. In data collection techniques, researchers used observation, interviews and documentation. The results of this research show that the communication model applied to improve the religious experience of converts in minority areas such as North Nias Regency is based on the principles of inclusiveness, continuous education and interfaith collaboration. The following are the components of this communication model: Open and Inclusive Dialogue, Continuous Religious Education, Use of Understandable Language, Social Media as a Communication Tool, Collaborative Interfaith Programs, Continuous Evaluation and Adjustment and Mentoring and Personal Support. In an effort to strengthen the religious experience of converts to Islam, the district has implemented various important steps. One of the main initiatives taken was the establishment of the Muallaf Empowerment Institute. This institution acts as a platform that provides comprehensive support to converts to Islam, especially in terms of assistance, training and guidance in understanding and implementing the teachings of the Islamic religion.